GASTRONOMIC EXPERIENCES IN TOURISM: A SYSTEMATIC LITERATURE REVIEW AND FUTURE RESEARCH DIRECTIONS - Ni Made Purnami; Andhy Setyawan (Adisam Publisher, 2025)
The purpose of this systematic literature review is to summarize existing research on the role of gastronomic experiences in tourism, focusing on the factors influencing these experiences, their impacts, and the various dimensions involved. Using the Scopus database, 19 studies published between 2020 and 2024 in Q1 and Q2 journals were reviewed. The review identifies key dimensions of gastronomic experiences, including sensory, intellectual, affective, food quality, service quality, and physical environment quality. The findings reveal that gastronomic experiences significantly influence destination image, tourist satisfaction, loyalty, happiness, food consumption emotions, experiential value, behavior intentions, trust, word of mouth, competitive destination, perceived value, place attachment, length of stay, and brand love. Recommendations for future research include exploring additional dimensions of gastronomic experiences, examining interrelationships between influencing factors, investigating demographic impacts, researching moderating and mediating effects, integrating technology in gastronomic tourism, and emphasizing sustainable practices. These insights provide valuable guidance for tourism stakeholders to enhance culinary offerings and better meet the evolving needs of tourists.